Recognition of dengue disease patterns using artificial neural networks - Cetiner, Beytullah Gultekin; Sari, Murat; Aburas, Hani M. (2009)
This research aimed at the recognition of the patterns for dengue disease patterns using Artificial Neural Networks (ANN’s). Real data was provided by Singaporean National Environment Agency (NEA), for academic purposes only. Obtained data was used to model the behavior of dengue cases based on the physical parameters of mean temperature, mean relative humidity and total rainfall. The set of data recorded weekly consists of dengue reported confirmed cases together with three aforementioned parameters and for a six-year period, January 2001 to April 2007.